Fluorinated biselenophene-naphthalenediimide copolymers for efficient all-polymer solar cells. (December 2020) - Shi, Shengbin; Luo, Jiasi; Wu, Ziang; Liu, Bin; Su, Mengyao; Chen, Peng; Zhang, Xianhe; Feng, Kui; Woo, Han Young; Xiao, Guomin
Abstract: Biselenophene (BS ) is generally considered as a promising building block for constructing organic semiconductors, and the 3-positions of selenophene in BS offer a great opportunity for further structural modification. Herein, a novel fluorinated biselenophene, 3, 3′-difluoro-2, 2′-biselenophene (BSF ), was designed and synthesized successfully, and subsequently incorporated into a polymer backbone leading to the resulting polymer PNDIBSF . The polymer backbone planarity was significantly improved via the enhanced intramolecular noncovalent Se⋯F coulombic interactions. Meanwhile, the electronic structure of the polymer was effectively tuned by the high electronegativity of F atoms. All-polymer solar cells (all-PSCs) with J71 and PNDIBSF as polymer donor and acceptor achieved power conversion efficiency (PCE) of 5.20%. In comparsion, all-PSCs based on the nonfluorinated analogue polymer acceptor (PNDIBS ) had low PCE of 2.74%. The results demonstrated that BSF is a promising building block for constructing polymer acceptor in all-PSCs, and the fluorination offers a sufficient strategy for further improving performance of selenophene-based polymer semiconductors. Graphical abstract: A new fluorinated biselenophene unit was synthesized to be applied to polymer semiconductors with high power conversion efficiency of 5.20% in all-polymer solar cells, and fluorination offers a sufficient strategy for further improving performance of selenophene-based polymer semiconductors. Image 1 Highlights: A novel fluorinated biselenophene was designed and synthesized successfully. Polymer backbone planarity was significantly improved via the noncovalent Se⋯F coulombic interactions. The fluorination leads to enhancements both in J SC and FF, with a PCE up to 5.20% in all-PSCs.